Forced labour in the Russian Federation today irregular migration and trafficking in human beings - Tjurjukanova, Elena Vladimirovna 1959- (International Labour Office, 2005)
Using a mix of qualitative and quantitative methods, examines the forms of exploitation and coercion imposed on migrant workers